Performance of investment when investors strictly follow analysts' recommendation. - Liao, Kelvin Wensheng. (2009)
This study seeks to investigate the relative performance of the investment portfolios formed when investors strictly follow the recommendations of analysts in the East Asian markets, namely Hong Kong, Korea and Taiwan. The study is conducted for the period between January 1997 to March 2008. Results showed that there are indications of analysts’ recommendations providing investors with valuable information, especially in Taiwan. Statistics have proved that Strong Buy and Buy Portfolio have outperformed other portfolios and this is further substantiated by Sharpe Ratios analysis. These results put to question as to whether investors can rely on analysts’ recommendations as a basis for formulating their investment strategy. Furthermore, it raises the issue as to how differently should an investor approach the various recommendations.